Teachers’ Feedback Learning Conceptions: Evidences from the Teaching Evaluation in Chile - Contreras Pérez, Gloria (2018)
The following article presents the results of an investigation carried out based on the analysis of two documents of the portfolio of the Teacher Evaluation System: a marked evaluation procedure of a student and the respective feedback that the teacher would give to that student in modality of dialogue. Its main objective was to characterize the type of feedback made by teachers and to infer the underlying conceptions. The study’s design was descriptive-exploratory and consisted of a documentary analysis based on pre-defined categories. In total, the evaluation procedures and feedback of 158 teachers presented in their portfolio in 2012 were analyzed. The results show that in the marked evaluation procedure, the feedback was directed to explain or justify the score and grade obtained by the student, which suggests a conception oriented to the correction. In the dialogue mode, feedback was directed to students’ ego, praising or congratulating him or her without being linked to their learning process, which implies a conception of feedback as a compliment. Also, it focuses on students’ work and on their errors or absences, suggesting a conception of feedback as a specification of failed learning, with little presence of suggestions for improvement. It is concluded that assessment feedback is far from being an educational tool that promotes permanent improvements in students learning.